Two-component spray unsaturated polyester resin putty and preparation method thereof

By preparing two-component spray-coated unsaturated polyester resin putty, using homemade resin and filler combination, the shortcomings of traditional putty in surface dryness and grinding are solved, and the rapid drying and excellent grinding of putty are achieved, meeting the efficient and high-quality construction needs.

CN118879113BActive Publication Date: 2025-03-14YINGDE RONGCHANG CHEM IND CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411188355.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-28
Publication Date
2025-03-14
Estimated Expiration
2044-08-28

AI Technical Summary

Technical Problem

Traditional unsaturated polyester resin putty has shortcomings in terms of surface dryness and polishing properties, and it is difficult to meet the needs of efficient and high-quality construction.

Method used

By preparing two-component spray-coated unsaturated polyester resin putty, using homemade resin and filler combination, linoleic acid and triethylene glycol are added to improve the surface dryness, and the grinding ability of the putty is improved through the matching and proportion adjustment of different fillers.

Benefits of technology

It realizes the rapid drying of putty, is easy to construct, has excellent grinding and long-term storage period, and meets the needs of efficient and high-quality construction.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005014237880000071
    Figure BDA0005014237880000071
Patent Text Reader

Abstract

The present invention relates to a two-component spraying unsaturated polyester resin putty and a preparation method thereof, belonging to the technical field of unsaturated polyester resin putty, and the preparation method comprises the following steps: S1, using phthalic anhydride, hexylene glycol, triethylene glycol, linoleic acid, propylene glycol, neopentyl glycol, a catalyst and maleic anhydride to make a self-made resin; S2, taking the self-made resin and adding zinc stearate, montmorillonite, precipitated white carbon black, titanium dioxide, accelerator, inhibitor, poly [1-(methoxycarbonylmethyl)ethylene] and styrene to prepare the main ash; S3, preparing a putty finished product. The present invention adds linoleic acid and triethylene glycol to accelerate the surface dryness of the putty; in addition, the present invention also uses zinc stearate, montmorillonite, precipitated white carbon black and titanium dioxide in combination, and synergistically improves the polishability of the unsaturated polyester resin putty. The addition of poly [1-(methoxycarbonylmethyl)ethylene] increases the anti-settling effect of the filler and prolongs the storage period of the finished product.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of unsaturated polyester resin putty, and specifically relates to a two-component spray unsaturated polyester resin putty and a preparation method thereof. Background Art

[0002] Putty is commonly known as putty, also known as unsaturated polyester resin putty. Putty is generally composed of a main agent and a curing agent, wherein the main agent generally includes UPR, accelerator, inhibitor and pigment filler, and the curing agent is generally an organic peroxide. As a mainstream repair and coating material, putty has the characteristics of easy shaping, good bonding performance and low cost. It is often used in the automotive field to quickly fill defects such as pits, cracks and small welds on the surface of the car body, for repairing and leveling the surface of ships, for filling cracks and damage in the construction field, and also used in decoration, engineering machinery and other fields. However, with the rapid development of modern industry and construction technology, the requirements for putty materials are increasing day by day. As an important treatment material before painting, the performance of putty directly affects the adhesion, aesthetics and durability of subsequent coatings. Traditional putty materials have many shortcomings in terms of surface dryness and polishability, such as long curing time and difficulty in polishing, which are difficult to meet the needs of efficient and high-quality construction. Therefore, it is particularly important to provide a two-component spray unsaturated polyester resin putty with excellent surface dryness and polishability. Summary of the invention

[0003] The purpose of the present invention is to provide a two-component spray unsaturated polyester resin putty and a preparation method thereof, so as to solve the problem that the unsaturated polyester resin putty in the prior art is lacking in surface dryness and polishability.

[0004] The purpose of the present invention can be achieved by the following technical solutions:

[0005] A method for preparing a two-component spray unsaturated polyester resin putty specifically comprises the following steps:

[0006] S1, homemade resin: phthalic anhydride, hexylene glycol, triethylene glycol, linoleic acid, propylene glycol, neopentyl glycol and a catalyst are mixed uniformly, nitrogen is introduced, the temperature is controlled and stirred, the acid value is measured once, maleic anhydride is added, the temperature is controlled and stirred, the acid value is measured again, and a vacuum pump is turned on for dehydration and deacidification to obtain a homemade resin;

[0007] S2, preparing main ash: taking the self-made resin, adding zinc stearate, montmorillonite, precipitated white carbon black and titanium dioxide, mixing evenly and stirring, then adding accelerator, inhibitor, poly [1- (methoxycarbonylmethyl) ethylene] and styrene, mixing evenly and continuing to stir, after the stirring is completed, kneading to obtain main ash;

[0008] S3, preparing the putty finished product: the main ash and cyclohexanone peroxide are mixed evenly to obtain the putty finished product.

[0009] As a preferred technical solution of the present invention, the mass ratio of phthalic anhydride, hexylene glycol, triethylene glycol, linoleic acid, propylene glycol, neopentyl glycol, catalyst and maleic anhydride in step S1 is 145-150:42-44:20-22:50-52:103-106:20-21:0.1-0.2:85-88.

[0010] Furthermore, the catalyst is dibutyltin dilaurate.

[0011] As a preferred technical solution of the present invention, the temperature of the temperature-controlled stirring in step S1 is 185-190°C.

[0012] As a preferred technical solution of the present invention, the mass ratio of the homemade resin, zinc stearate, montmorillonite, precipitated silica, titanium dioxide, accelerator, inhibitor, poly[1-(methoxycarbonylmethyl)ethylene] and styrene in step S2 is 38-42:1.5-2:2-4:3-5:15-20:2-3:0.1-0.2:1-1.2:2-2.5.

[0013] Furthermore, the promoter is cobalt naphthoate; and the inhibitor is hydroquinone.

[0014] Furthermore, the montmorillonite is 300 mesh; the precipitated silica is 325 mesh; and the titanium dioxide is 800 mesh.

[0015] As a preferred technical solution of the present invention, the time for uniform mixing and stirring in step S2 is 0.5-1h; the time for continued stirring is 45-60min; and the time for kneading is 2-3h.

[0016] As a preferred technical solution of the present invention, the mass ratio of the main ash and cyclohexanone peroxide in step S3 is 50:1.

[0017] As a preferred technical solution of the present invention, the present invention also provides a putty prepared by the preparation method of the above-mentioned two-component spray unsaturated polyester resin putty.

[0018] Beneficial effects of the present invention:

[0019] (1) The present invention adds a linoleic acid compound with a double bond in the molecule, and the hydrogen in the linoleic acid compound can undergo an oxygen-abstracting reaction in the air to produce free radicals. On this basis, triethylene glycol is added for modification, and a continuous ether bond structure is introduced, which accelerates the system to absorb oxygen in the air, thereby accelerating the surface drying of the putty. Therefore, the putty prepared in this way has a fast drying speed, is easy to construct, and is extremely practical.

[0020] (2) The present invention uses different types of fillers in combination and adjusts the ratio between the fillers, synergistically improving the polishability of unsaturated polyester resin putty. Specifically, zinc stearate with good wettability reduces the friction difficulty between the putty and the polishing tool; montmorillonite with high surface activity and lamellar structure inhibits the expansion of microcracks, thereby improving the wear resistance and impact resistance of the putty and indirectly improving the polishability; precipitated silica provides reinforcement and filling; titanium dioxide fills the tiny gaps and defects in the putty, forming a good interface bond with it, which helps to improve the overall stability of the putty; therefore, the putty prepared in this way has excellent polishability.

[0021] (3) The present invention adds poly[1-(methoxycarbonylmethyl)ethylene], which can effectively form a three-dimensional structure with the homemade resin, so that the filler used in the present invention is stably suspended in the structure, thereby increasing the anti-settling effect of the filler and more effectively extending the stability and storage period of the finished product. DETAILED DESCRIPTION

[0022] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0023] Example 1

[0024] A method for preparing a two-component spray unsaturated polyester resin putty specifically comprises the following steps:

[0025] S1, homemade resin: phthalic anhydride, hexylene glycol, triethylene glycol, linoleic acid, propylene glycol, neopentyl glycol and dibutyltin dilaurate were mixed evenly, nitrogen was introduced, the temperature was controlled at 190°C and stirred, the acid value was measured once, and maleic anhydride was added when the acid value reached 95 mgKOH / g, the temperature was controlled at 185°C and stirred for a second time, the acid value was measured for a second time, the reaction reached an acid value of 45 mg KOH / g, and a vacuum pump was turned on for dehydration and deacidification to obtain a homemade resin;

[0026] The mass ratio of phthalic anhydride, hexylene glycol, triethylene glycol, linoleic acid, propylene glycol, neopentyl glycol, catalyst and maleic anhydride is 148:42:20:52:103:21:0.1:85;

[0027] S2, preparing main ash: taking the self-made resin, adding zinc stearate, 300 mesh montmorillonite, 325 mesh precipitated white carbon black and 800 mesh titanium dioxide, mixing evenly and stirring for 1 hour, then adding cobalt naphthoate, hydroquinone, poly [1- (methoxycarbonylmethyl) ethylene] and styrene, mixing evenly and continuing to stir for 45 minutes, and kneading for 2.5 hours after the stirring is completed to obtain the main ash;

[0028] The mass ratio of the self-made resin, zinc stearate, montmorillonite, precipitated silica, titanium dioxide, accelerator, inhibitor, poly[1-(methoxycarbonylmethyl)ethylene] and styrene is 38:1.5:2:5:17.5:2.5:0.1:1:2;

[0029] S3. Prepare the finished putty product: evenly mix the main ash and cyclohexanone peroxide in a mass ratio of 50:1 to obtain the finished putty product.

[0030] Example 2

[0031] A method for preparing a two-component spray unsaturated polyester resin putty specifically comprises the following steps:

[0032] S1, homemade resin: phthalic anhydride, hexylene glycol, triethylene glycol, linoleic acid, propylene glycol, neopentyl glycol and dibutyltin dilaurate were mixed evenly, nitrogen was introduced, the temperature was controlled at 185°C and stirred, the acid value was measured once, and maleic anhydride was added when the acid value reached 90 mgKOH / g, the temperature was controlled at 187°C and stirred for a second time, the acid value was measured for a second time, the reaction reached an acid value of 50 mg KOH / g, and a vacuum pump was turned on for dehydration and deacidification to obtain a homemade resin;

[0033] The mass ratio of phthalic anhydride, hexylene glycol, triethylene glycol, linoleic acid, propylene glycol, neopentyl glycol, catalyst and maleic anhydride is 145:44:21:50:104.5:20:0.15:88;

[0034] S2, preparing main ash: taking the self-made resin, adding zinc stearate, 300 mesh montmorillonite, 325 mesh precipitated white carbon black and 800 mesh titanium dioxide, mixing evenly and stirring for 0.5h, then adding cobalt naphthoate, hydroquinone, poly[1-(methoxycarbonylmethyl)ethylene] and styrene, mixing evenly and continuing to stir for 57min, after the stirring is completed, kneading for 3h to obtain the main ash;

[0035] The mass ratio of the self-made resin, zinc stearate, montmorillonite, precipitated silica, titanium dioxide, accelerator, inhibitor, poly[1-(methoxycarbonylmethyl)ethylene] and styrene is 42:2:3:3:20:2:0.2:1.1:2.25;

[0036] S3. Prepare the finished putty product: evenly mix the main ash and cyclohexanone peroxide in a mass ratio of 50:1 to obtain the finished putty product.

[0037] Example 3

[0038] A method for preparing a two-component spray unsaturated polyester resin putty specifically comprises the following steps:

[0039] S1, homemade resin: phthalic anhydride, hexylene glycol, triethylene glycol, linoleic acid, propylene glycol, neopentyl glycol and dibutyltin dilaurate were mixed evenly, nitrogen was introduced, the temperature was controlled at 187°C and stirred, the acid value was measured once, and maleic anhydride was added when the acid value reached 100 mgKOH / g, the temperature was controlled at 190°C and stirred for a second time, the acid value was measured for a second time, the reaction reached an acid value of 40 mg KOH / g, and a vacuum pump was turned on for dehydration and deacidification to obtain a homemade resin;

[0040] The mass ratio of phthalic anhydride, hexylene glycol, triethylene glycol, linoleic acid, propylene glycol, neopentyl glycol, catalyst and maleic anhydride is 150:43:22:51:106:20.5:0.2:87.5;

[0041] S2, preparing main ash: taking the self-made resin, adding zinc stearate, 300 mesh montmorillonite, 325 mesh precipitated white carbon black and 800 mesh titanium dioxide, mixing evenly and stirring for 1 hour, then adding cobalt naphthoate, hydroquinone, poly [1- (methoxycarbonylmethyl) ethylene] and styrene, mixing evenly and continuing to stir for 60 minutes, and kneading for 2 hours after the stirring is completed to obtain the main ash;

[0042] The mass ratio of the self-made resin, zinc stearate, montmorillonite, precipitated white carbon black, titanium dioxide, accelerator, inhibitor, poly[1-(methoxycarbonylmethyl)ethylene] and styrene is 40:1.7:4:4:15:3:0.15:1.2:2.5

[0043] S3. Prepare the finished putty product: evenly mix the main ash and cyclohexanone peroxide in a mass ratio of 50:1 to obtain the finished putty product.

[0044] Comparative Example 1

[0045] Compared with Example 1, the difference is that no linoleic acid is added in Comparative Example 1, and the other operating steps and parameters remain unchanged.

[0046] Comparative Example 2

[0047] Compared with Example 1, the difference is that triethylene glycol is not added in Comparative Example 2, and the other operating steps and parameters remain unchanged.

[0048] Comparative Example 3

[0049] Compared with Example 1, the difference is that zinc stearate is not added in Comparative Example 3, that is, the mass ratio of the homemade resin, montmorillonite, precipitated silica, titanium dioxide, accelerator, inhibitor, poly[1-(methoxycarbonylmethyl)ethylene] and styrene in step S2 is 38:2.5:5.5:18:2.5:0.1:1:2; the other operating steps and parameters remain unchanged.

[0050] Comparative Example 4

[0051] Compared with Example 1, the difference is that no montmorillonite is added in Comparative Example 4, that is, the mass ratio of the homemade resin, zinc stearate, precipitated silica, titanium dioxide, accelerator, inhibitor, poly[1-(methoxycarbonylmethyl)ethylene] and styrene in step S2 is 38:2.2:5.7:18.1:2.5:0.1:1:2; the other operating steps and parameters remain unchanged.

[0052] Comparative Example 5

[0053] Compared with Example 1, the difference is that no precipitated silica is added in Comparative Example 5, that is, the mass ratio of the homemade resin, zinc stearate, montmorillonite, titanium dioxide, accelerator, inhibitor, poly[1-(methoxycarbonylmethyl)ethylene] and styrene in step S2 is 38:3.2:3.7:19.1:2.5:0.1:1:2; the other operating steps and parameters remain unchanged.

[0054] Comparative Example 6

[0055] Compared with Example 1, the difference is that titanium dioxide is not added in Comparative Example 6, that is, the mass ratio of the homemade resin, zinc stearate, montmorillonite, precipitated silica, accelerator, inhibitor, poly[1-(methoxycarbonylmethyl)ethylene] and styrene in step S2 is 38:7.4:7.9:10.7:2.5:0.1:1:2; the other operating steps and parameters remain unchanged.

[0056] Comparative Example 7

[0057] Compared with Example 1, the difference is that in Comparative Example 7, poly[1-(methoxycarbonylmethyl)ethylene] is not added, and the other operating steps and parameters remain unchanged.

[0058] Test Case

[0059] (1) According to GB / T 1728-1979 (1989) "Determination of Drying Time of Paint Film and Putty Film", the surface drying time of the two-component spray unsaturated polyester resin putty prepared in Examples 1-3 and Comparative Examples 1-2 was tested. The results are shown in Table 1.

[0060] (2) The two-component spray unsaturated polyester resin putty prepared in Examples 1-3 and Comparative Examples 3-6 was tested for its polishability according to GB / T 1770-2008 “Test Method for Polishability of Coating and Putty Films”. The results are shown in Table 1.

[0061] (3) 5 kg of the two-component spray unsaturated polyester resin putty prepared in Examples 1-3 and Comparative Example 7 was placed in a sealed galvanized iron drum and stored at 28° C. The actual storage period was tested. The time judgment standard was the storage validity period during which the resin and filler were not separated or could be redispersed into the product by slight manual stirring after separation. The results are shown in Table 1.

[0062] Table 1

[0063]

[0064]

[0065] It can be seen from the data of Examples 1-3 and Comparative Examples 1-2 in Table 1 that the putty prepared by the present invention has a fast drying speed, is easy to construct, and is extremely practical; and it can be seen from the data of Examples 1-3 and Comparative Examples 3-6 that the present invention uses different types of fillers in combination and adjusts the ratio between the fillers, which synergistically improves the polishability of the unsaturated polyester resin putty. Therefore, the putty prepared by the method of the present invention has excellent polishability; It can be seen from the data of Examples 1-3 and Comparative Example 7 that the putty prepared by the present invention has the characteristics of long-term storage.

[0066] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0067] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. A method for preparing a two-component spray unsaturated polyester resin putty, characterized in that: The specific steps include: S1, homemade resin: phthalic anhydride, hexylene glycol, triethylene glycol, linoleic acid, propylene glycol, neopentyl glycol and a catalyst are mixed uniformly, nitrogen is introduced, the temperature is controlled and stirred, the acid value is measured once, maleic anhydride is added, the temperature is controlled and stirred, the acid value is measured again, and a vacuum pump is turned on for dehydration and deacidification to obtain a homemade resin; S2, preparing main ash: taking the self-made resin, adding zinc stearate, montmorillonite, precipitated white carbon black and titanium dioxide, mixing evenly and stirring, then adding accelerator, inhibitor, poly [1- (methoxycarbonylmethyl) ethylene] and styrene, mixing evenly and continuing to stir, after the stirring is completed, kneading to obtain main ash; S3, preparing the putty finished product: mixing the main ash and cyclohexanone peroxide evenly to obtain the putty finished product; In step S1, the mass ratio of phthalic anhydride, hexylene glycol, triethylene glycol, linoleic acid, propylene glycol, neopentyl glycol, catalyst and maleic anhydride is 145-150:42-44:20-22:50-52:103-106:20-21:0.1-0.2:85-88; The mass ratio of the self-made resin, zinc stearate, montmorillonite, precipitated silica, titanium dioxide, accelerator, inhibitor, poly[1-(methoxycarbonylmethyl)ethylene] and styrene in step S2 is 38-42:1.5-2:2-4:3-5:15-20:2-3:0.1-0.2:1-1.2:2-2.5; The montmorillonite has a mesh size of 300; the precipitated white carbon black has a mesh size of 325; and the titanium dioxide has a mesh size of 800.

2. The method for preparing a two-component spray unsaturated polyester resin putty according to claim 1, characterized in that: The catalyst is dibutyltin dilaurate.

3. The preparation method of the two-component spray unsaturated polyester resin putty according to claim 1, characterized in that: The temperature of the temperature-controlled stirring in step S1 is 185-190°C.

4. The method for preparing a two-component spray unsaturated polyester resin putty according to claim 1, characterized in that: The promoter is cobalt naphthoate; and the inhibitor is hydroquinone.

5. The method for preparing a two-component spray unsaturated polyester resin putty according to claim 1, characterized in that: The mixing and stirring time in step S2 is 0.5-1h; the stirring time is 45-60min; and the kneading time is 2-3h.

6. The method for preparing a two-component spray unsaturated polyester resin putty according to claim 1, characterized in that: The mass ratio of the main ash to cyclohexanone peroxide in step S3 is 50:

1.

7. A putty prepared by the method for preparing a two-component spray unsaturated polyester resin putty as described in any one of claims 1 to 6.

Citation Information

Patent Citations

  • Environment-friendly aqueous putty

    CN101570655A

  • High-tensile strength modified unsaturated polyester resin and preparation method thereof

    CN106751347A

  • Unsaturated polyester resin putty composition for powder coating technology and preparation method of unsaturated polyester resin putty composition

    CN115851086A